The development, validation and application of an electronics laboratory environment inventory in Indonesia - Liawatimena, Suryadiputra (Curtin University, 2004)
This study investigates and describes the development of an instrument named the Electronics Laboratory Environment Inventory (ELEI), which is used to measure students' perceptions of the electronics laboratory class as a learning environment. The sample consisted of 353 of 708 Computer Engineering active students from eight classes in Bina Nusantara University, Jakarta, Indonesia. Bina Nusantara University which has the largest number of computer engineering students in Indonesia. Students' learning outcomes were measured using z-scores in electronics subjects and students' attitudes in laboratory classes were measured by using the Attitude Towards Electronics Questionnaire (ATEQ). Directed by the research questions, numerous statistical analyses were performed. These included item analysis, inter-item correlation analysis, one-way analysis of variance for establishing reliability and validity of the laboratory class environment instruments in the present study; descriptive statistics for investigating the nature of the learning environment in electronics subjects; simple and multiple correlation analyses for investigating associations between laboratory class environment and students' outcomes. In all cases, electronics laboratory classes have played a major role. The scales measured Student Cohesiveness, Open-endedness, Integration, Technology Adequacy, and Laboratory Availability. The results showed that all five scales have a reasonable alpha reliability with low mean correlations.The study discovered that, generally, students perceived their electronics class learning environments as favourable. It was found that students' perceptions of electronics laboratory class environment were associated with students' learning outcomes. The results of this study make important and unique contributions to students' learning outcomes, suggesting that the instruments are useful for assessing laboratory class environment in the other studies.